Electrolyte, battery, energy storage device and energy storage system
By adding phenylsulfonylimidazoles and boron-containing lithium salts to the electrolyte of lithium-ion batteries, the problem of low circulation capacity retention rate of lithium-ion batteries at high temperatures is solved, and higher high-temperature circulation performance and more stable SEI membrane.
Patent Information
- Application Number
- CN202411664268.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-20
- Publication Date
- 2025-02-14
AI Technical Summary
The existing lithium-ion batteries have low circulation capacity retention rates at high temperatures and have poor performance in wide temperatures and long life.
An electrolyte solution is used, which includes an electrolyte salt, phenylsulfonylimidazoles and a boron-containing lithium salt. Through these additives, a reduction reaction is preferred on the surface of the negative electrode sheet to generate phenyl radicals and sulfonyl imidazoles, which promote the ring opening of the cyclic carbonate, form a stable lithium carbonate inorganic salt, and improve the stability of the SEI film.
It improves the high-temperature cycling performance of the battery, enhances the stability and heat resistance of the SEI film, and extends the service life of the battery.
Smart Images

Figure CN119447463A_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the field of energy storage, and specifically to an electrolyte, a battery, an energy storage device and an energy storage system. Background Art
[0002] With the continuous development of lithium-ion battery technology, lithium-ion batteries have the advantages of large specific capacity, no memory effect, high operating voltage, fast charging speed, wide operating temperature range, long cycle life, small size, light weight, etc. compared with other types of batteries such as lead-acid, cadmium nickel, etc. At present, lithium-ion batteries have been widely used in mobile phones, laptops, electric vehicles, energy storage cabinets and other fields, and their application range is becoming more and more extensive.
[0003] With the development of the energy storage industry, higher requirements are placed on the life attenuation and service life of lithium-ion batteries. However, the existing lithium-ion batteries have a low cycle capacity retention rate at high temperatures and poor wide temperature and long life performance. Summary of the invention
[0004] The embodiment of the present application provides an electrolyte, which, when applied to a battery, can enable the battery to have higher high-temperature cycle performance.
[0005] In a first aspect, an embodiment of the present application provides an electrolyte solution, wherein the electrolyte solution includes an electrolyte salt, phenylsulfonyl imidazoles, and a boron-containing lithium salt.
[0006] In some embodiments, the phenylsulfonyl imidazoles have the following structural formula:
[0007]
[0008] Wherein, R1 is at least one of hydrogen, fluorine, methyl, trifluoromethyl, phenyl, isocyanate group, and vinyl group;
[0009] R2 is at least one of hydrogen, fluorine, methyl, trifluoromethyl, phenyl, isocyanate, and vinyl;
[0010] R3 is at least one of hydrogen, fluorine, methyl, trifluoromethyl, phenyl, isocyanate, and vinyl;
[0011] R4 is at least one of hydrogen, fluorine, methyl, trifluoromethyl, phenyl, isocyanate, and vinyl;
[0012] R5 is at least one of hydrogen, fluorine, methyl, trifluoromethyl, phenyl, isocyanate, and vinyl.
[0013] In some embodiments, the phenylsulfonyl imidazole is a p-substituted phenylsulfonyl imidazole, and the substituent is one of an electron withdrawing group, a conjugated group, and a reactive group.
[0014] In some embodiments, the phenylsulfonyl imidazoles include at least one of the following structural formulas:
[0015]
[0016] In some embodiments, the boron-containing lithium salt includes at least one of lithium tetrafluoroborate, lithium bis(oxalatoborate), and lithium difluorooxalatoborate.
[0017] In some embodiments, in the electrolyte, the mass ratio A of the phenylsulfonyl imidazole to the boron-containing lithium salt is in the range of 0.05≤A≤4.0.
[0018] In some embodiments, in the electrolyte, the mass ratio A of the phenylsulfonyl imidazole to the boron-containing lithium salt is in the range of 0.6≤A≤2.
[0019] In some embodiments, in the electrolyte, the mass fraction a of the phenylsulfonyl imidazole is in the range of 0.05%≤a≤2.0%.
[0020] In some embodiments, in the electrolyte, the mass fraction b of the boron-containing lithium salt is in the range of 0.05%≤b≤2.0%.
[0021] In a second aspect, an embodiment of the present application further provides a battery, which includes: the electrolyte, the positive electrode plate, the separator and the negative electrode plate described in the embodiment of the present application.
[0022] In a third aspect, an embodiment of the present application further provides an energy storage device, comprising:
[0023] The housing; and
[0024] A plurality of batteries according to the second aspect of the present application are contained in the box.
[0025] In a fourth aspect, an embodiment of the present application further provides an energy storage system, which includes:
[0026] The energy storage device described in the third aspect of the present application; and
[0027] An electric energy conversion device, wherein the electric energy conversion device is electrically connected to the energy storage device, the electric energy conversion device is used to convert other forms of energy into electric energy, and the energy storage device is used to store the electric energy.
[0028] The electrolyte of the embodiment of the present application includes phenylsulfonyl imidazoles and boron-containing lithium salts. The additive phenylsulfonyl imidazole contains S elements and N elements, and can preferentially undergo a reduction reaction on the surface of the negative electrode plate. The SC bond preferentially breaks to generate phenyl radicals and sulfonyl imidazoles. The phenyl radicals can promote the ring opening of ethylene carbonate (EC) in the cyclic carbonate in the electrolyte, which is beneficial to the formation of lithium carbonate inorganic salts from ethylene carbonate on the surface of the negative electrode plate. The lithium carbonate inorganic salt can improve the stability of the SEI film, thereby improving the high-temperature cycle performance of the SEI film. In addition, when phenylsulfonyl imidazoles participate in the formation of SEI films, there are multi-step reactions, which are not conducive to the construction of SEI films of negative electrode sheets; the lone pair of electrons on the N atom of the imidazole ring in phenylsulfonyl imidazoles does not participate in conjugation, has nucleophilicity, and interacts with the electron-deficient B atom in the boron-containing lithium salt, thereby achieving the regulation of the reaction decomposition path of phenylsulfonyl imidazoles. Therefore, after adding boron-containing lithium salts, the reaction of phenylsulfonyl imidazoles can be made more single, and the thickness uniformity of the generated SEI film will be better, making the impedance distribution of the SEI film more uniform, and less prone to partial lithium analysis (because lithium precipitation is prone to occur in places where the barrier is too large), thereby improving the stability of the SEI film. Furthermore, boron-containing lithium salts are conducive to the formation of SEI films rich in nitrogen and sulfur elements on the surface of the negative electrode sheet. SEI films rich in nitrogen and sulfur elements have higher high temperature tolerance, which can better improve the cycle performance of the battery. Furthermore, by using phenylsulfonyl imidazole and boron-containing lithium salt additives together, the SEI film formed on the surface of the negative electrode can contain imidazole organic polymers, phenyl organic polymers, Li3N and lithium sulfate. Imidazole organic polymers and phenyl organic polymers are beneficial to improving the flexibility of the SEI film and reducing the possibility of rupture of the SEI film during repeated lithium insertion and de-lithiation, thereby improving the high-temperature cycle performance of the battery. Inorganic salts such as Li3N and lithium sulfate can improve the heat resistance of the SEI film and reduce the solubility of the SEI film, thereby further improving the high-temperature cycle performance of the battery. BRIEF DESCRIPTION OF THE DRAWINGS
[0029] In order to more clearly illustrate the technical solutions of the embodiments of the present application, the drawings required for use in the embodiments will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present application. For ordinary technicians in this field, other drawings can be obtained based on these drawings without creative work.
[0030] Figure 1 It is a structural block diagram of an energy storage system according to an embodiment of the present application.
[0031] Figure 2 This is an application scenario diagram of an energy storage system according to an embodiment of the present application.
[0032] Figure 3It is a schematic structural diagram of an energy storage device according to an embodiment of the present application.
[0033] Figure 4 It is a schematic diagram of the structure of a battery according to an embodiment of the present application.
[0034] Figure 5 The battery of one embodiment of the present application is Figure 4 Schematic diagram of the cross-sectional structure in the AA direction.
[0035] Figure 6 It is a schematic diagram of the structure of the positive electrode plate of one embodiment of the present application.
[0036] Figure 7 It is a schematic diagram of the structure of the negative electrode plate of one embodiment of the present application.
[0037] Description of reference numerals:
[0038] 100 -battery, 110 -positive electrode plate, 111 -positive current collector, 112 -positive electrode active layer, 120 -diaphragm, 130 -negative electrode plate, 131 -negative current collector, 132 -negative electrode active layer, 140 -housing, 150 -end cover assembly, 141 -receiving chamber, 200 -energy storage device, 210 -casing, 300 -energy storage system, 310 -electric energy conversion device. DETAILED DESCRIPTION
[0039] In order to enable those skilled in the art to better understand the solution of the present application, the technical solution in the embodiments of the present application will be clearly and completely described below in conjunction with the drawings in the embodiments of the present application. Obviously, the described embodiments are only part of the embodiments of the present application, not all of the embodiments. Based on the embodiments in the present application, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of this application.
[0040] The terms "first", "second", etc. in the specification and claims of this application and the above-mentioned drawings are used to distinguish different objects, rather than to describe a specific order. In addition, the terms "including" and "having" and any variations thereof are intended to cover non-exclusive inclusions. For example, a process, method, system, product or device that includes a series of steps or units is not limited to the listed steps or units, but optionally includes steps or units that are not listed, or optionally includes other steps or units inherent to these processes, methods, products or devices.
[0041] The technical solutions in the embodiments of the present application will be described below in conjunction with the accompanying drawings.
[0042] It should be noted that, for the convenience of explanation, in the embodiments of the present application, the same figure marks represent the same components, and for the sake of brevity, detailed descriptions of the same components are omitted in different embodiments.
[0043] At present, the generation of green electricity generally relies on photovoltaics, wind power, and hydropower, etc. However, wind and solar energy generally have problems of strong intermittency and large volatility, which will cause instability in the power grid, insufficient electricity during peak hours, and too much electricity during valley hours. Unstable voltage will also cause damage to electricity. Therefore, insufficient electricity demand or insufficient grid acceptance capacity may cause the problem of "abandoning wind and solar power". To solve these problems, we must rely on energy storage. That is, converting electrical energy into other forms of energy through physical or chemical means and storing it, and converting energy into electrical energy and releasing it when needed. In simple terms, energy storage is like a large "power bank". When photovoltaic and wind energy are sufficient, electrical energy is stored and the stored electricity is released when needed.
[0044] The current energy storage (i.e., energy storage) application scenarios are relatively broad, including power generation side energy storage, grid side energy storage, and power consumption side energy storage. The following uses power generation side energy storage as an example to describe the energy storage system of the embodiment of the present application in detail, which should not be understood as a limitation on the energy storage system of the embodiment of the present application.
[0045] See also Figure 1 and Figure 2 The embodiment of the present application also provides an energy storage system 300, which includes: an electric energy conversion device 310 and the energy storage device 200 described in the embodiment of the present application, the electric energy conversion device 310 is electrically connected to the energy storage device 200, the electric energy conversion device 310 is used to convert other forms of energy into electric energy, and the energy storage device 200 is used to store the electric energy.
[0046] Optionally, the electric energy conversion device 310 can convert at least one other form of energy such as solar energy, light energy, wind energy, thermal energy, tidal energy, biomass energy and mechanical energy into electric energy.
[0047] Optionally, the number of the electric energy conversion devices 310 may be one or more. When there are multiple electric energy conversion devices 310, the multiple electric energy conversion devices 310 may be connected in series, in parallel, or in mixed connection, which is not specifically limited in the present application.
[0048] Optionally, the electric energy conversion device 310 may be, but is not limited to, at least one of a photovoltaic panel, a wind power generation device, a hydropower generation device, and the like.
[0049] Optionally, the number of the energy storage devices 200 may be one or more. When the number of the energy storage devices 200 is multiple, the multiple energy storage devices 200 are connected in series or in parallel, which is not specifically limited in the present application.
[0050] When working, the power conversion device 310 is used to convert other forms of energy into electrical energy and store it in the energy storage device 200. The electrical energy stored in the energy storage device 200 can be supplied to electrical loads such as street lamps and household appliances for use when the electricity price is at a peak, or to supply power when the power grid is out of power. The electrical energy generated by the power conversion device 310 can also be supplied to the power grid through high-voltage cables to alleviate the power supply pressure of the power grid during peak hours.
[0051] See also Figure 3 The embodiment of the present application further provides an energy storage device 200 , which includes a box 210 and a plurality of batteries 100 , wherein the plurality of batteries 100 are stacked and accommodated in the box 210 .
[0052] The term "plurality" means greater than or equal to two.
[0053] It can be understood that the multiple batteries 100 of the energy storage device 200 can be connected in parallel with each other; or in series with each other; or partially in parallel and partially in series (in other words, mixed connection). This application does not make any specific restrictions on the connection method of multiple batteries 100 of the same energy storage device 200.
[0054] Optionally, the energy storage device may be at least one of a small energy storage box, a large energy storage cabinet, an energy storage module, etc. The present application does not specifically limit the form of the energy storage device. The form of the energy storage device of the present application is only one of its many forms and should not be understood as a limitation on the energy storage device of the present application.
[0055] It can be understood that the box body 210 has a receiving cavity (not shown), and multiple batteries 100 are received in the receiving cavity. In some embodiments, each receiving cavity receives one battery 100. In other embodiments, each receiving cavity receives multiple batteries 100.
[0056] With the continuous development of lithium-ion battery technology, lithium-ion batteries have the advantages of large specific capacity, no memory effect, high operating voltage, fast charging speed, wide operating temperature range, long cycle life, small size, light weight, etc. compared with other types of batteries such as lead-acid, cadmium nickel, etc. At present, lithium-ion batteries have been widely used in mobile phones, laptops, electric vehicles, energy storage cabinets and other fields, and their application range is becoming more and more extensive.
[0057] With the development of the energy storage industry, higher requirements are placed on the life attenuation and service life of lithium-ion batteries. However, the existing lithium-ion batteries have a low cycle capacity retention rate at high temperatures and poor wide temperature and long life performance.
[0058] Battery degradation is mainly caused by the reaction of lithium ions on the surface of the negative electrode of the battery. First, during charging, ester solvents are easily reduced on the surface of the low-potential negative electrode and react with lithium, thereby consuming active lithium; secondly, the negative active layer of the negative electrode is constantly expanding and shrinking during the process of lithium extraction, causing the solid electrolyte interface membrane (SEI) on the surface of the negative active layer to be constantly pulled, exposing a new interface that continuously reacts with the electrolyte, resulting in the loss of active lithium. At high temperatures, the reaction between the surface of the negative electrode and the electrolyte is further intensified, and the interface stability of the negative electrode is further reduced, which greatly reduces the high-temperature cycle performance of the battery.
[0059] See also Figure 4 and Figure 5 The embodiment of the present application provides a battery 100 , which includes an electrolyte, a positive electrode plate 110 , a separator 120 and a negative electrode plate 130 , wherein the separator 120 is located between the positive electrode plate 110 and the negative electrode plate 130 .
[0060] It should be noted that the positive electrode sheet 110 and the negative electrode sheet 130 are at least partially immersed in the electrolyte.
[0061] It can be understood that the positive electrode sheet 110, the separator 120 and the negative electrode sheet 130 are stacked in sequence to form an electrode assembly. The electrode assembly can be, but is not limited to, a winding structure, a laminated structure, etc., which is not specifically limited in the present application.
[0062] It should be noted that the positive electrode sheet 110 and the negative electrode sheet 130 may be collectively referred to as electrode sheets. In other words, the electrode sheets include the positive electrode sheet 110 and the negative electrode sheet 130 .
[0063] See also Figure 6 Optionally, the positive electrode sheet 110 includes a positive current collector 111 and a positive active layer 112, and the positive active layer 112 is disposed on the surface of the positive current collector 111. It can be understood that the positive active layer 112 can cover one surface or two opposite surfaces of the positive current collector 111.
[0064] Optionally, the positive electrode current collector 111 may be, but is not limited to, an aluminum sheet.
[0065] Optionally, the positive electrode active layer 112 includes a positive electrode active material, a positive electrode conductor, a positive electrode binder and a positive electrode thickener.
[0066] Optionally, the positive electrode active material may be, but is not limited to, lithium iron phosphate.
[0067] Optionally, the positive electrode conductive agent may be, but is not limited to, at least one of conductive carbon black, acetylene black, carbon nanotubes, carbon fibers, graphene, and the like.
[0068] Optionally, the positive electrode binder may be, but is not limited to, at least one of polyvinylidene fluoride (PVDF), polyamide (PA), polyacrylonitrile (PAN), polyacrylate, polyvinylether, polymethyl methacrylate (PMMA), polyhexafluoropropylene, and styrene butadiene rubber (SBR).
[0069] Optionally, in the positive electrode active layer 112, the mass fraction of the positive electrode binder ranges from 2wt% to 4wt%. Specifically, in the positive electrode active layer 112, the mass fraction of the positive electrode binder may be, but is not limited to, 2wt%, 2.5wt%, 3wt%, 3.5wt%, 4wt%, etc. If the mass fraction of the positive electrode binder is too small, the positive electrode active layer 112 is prone to pulverization or slag; if the mass fraction of the positive electrode binder is too large, the energy density of the positive electrode sheet 110 is reduced.
[0070] Optionally, the positive electrode thickener may be, but is not limited to, at least one of sodium carboxymethyl cellulose (CMC for short), polyacrylamide (PAM) and polymethacrylate (PMA).
[0071] Optionally, the diaphragm 120 may be, but is not limited to, at least one of a polypropylene film (PP film for short), a polyethylene film (PE film for short), a ceramic diaphragm 120 , and the like.
[0072] Optionally, the thickness of the diaphragm 120 is 14 μm to 18 μm. Specifically, the thickness of the diaphragm 120 may be, but is not limited to, 14 μm, 14.5 μm, 15 μm, 15.5 μm, 16 μm, 16.5 μm, 17 μm, 17.5 μm, 18 μm, etc.
[0073] See also Figure 7 Optionally, the negative electrode sheet 130 includes a negative electrode current collector 131 and a negative electrode active layer 132, and the negative electrode active layer 132 is disposed on the surface of the negative electrode current collector 131. It can be understood that the negative electrode active layer 132 can cover one surface or two opposite surfaces of the negative electrode current collector 131.
[0074] Optionally, the negative electrode current collector 131 may be, but is not limited to, a copper sheet.
[0075] Optionally, the negative electrode active layer 132 includes a negative electrode active material, a negative electrode conductor, a negative electrode binder and a negative electrode thickener.
[0076] Optionally, the negative electrode active material may be, but is not limited to, graphite.
[0077] Optionally, the negative electrode conductive agent may be, but is not limited to, at least one of conductive carbon black (SP for short), acetylene black, carbon nanotubes, carbon fibers, graphene, and the like.
[0078] Optionally, the negative electrode binder may be, but is not limited to, at least one of polyvinylidene fluoride, polyamide, polyacrylonitrile, polyacrylate, polyvinyl ether, polymethyl methacrylate, polyhexafluoropropylene, styrene-butadiene rubber, and the like.
[0079] Optionally, in the negative electrode active layer 132, the mass fraction of the negative electrode binder ranges from 2wt% to 4wt%. Specifically, in the negative electrode active layer 132, the mass fraction of the negative electrode binder may be, but is not limited to, 2wt%, 2.5wt%, 3wt%, 3.5wt%, 4wt%, etc. If the mass fraction of the negative electrode binder is too small, the negative electrode active layer 132 is prone to pulverization or slag; if the mass fraction of the negative electrode binder is too large, the energy density of the negative electrode plate 130 is reduced.
[0080] Optionally, the negative electrode thickener may be, but is not limited to, at least one of sodium carboxymethyl cellulose (CMC for short), polyacrylamide (PAM) and polymethacrylate (PMA).
[0081] Please see again Figure 4 and Figure 5 Optionally, the battery 100 further includes a shell 140 and an end cover assembly 150 , wherein the shell 140 and the end cover assembly 150 enclose a receiving cavity 141 , and the receiving cavity 141 is used to receive the electrolyte, the positive electrode plate 110 , the diaphragm 120 and the negative electrode plate 130 .
[0082] The embodiment of the present application also provides an electrolyte, which includes an electrolyte salt, phenylsulfonyl imidazoles and a boron-containing lithium salt.
[0083] It should be noted that phenylsulfonyl imidazoles and boron-containing lithium salts are both added to the electrolyte as additives to improve the SEI film of the electrolyte and enhance the thermal stability of the SEI film, thereby enhancing the high temperature cycle performance of the battery 100 .
[0084] The electrolyte of the embodiment of the present application includes phenylsulfonyl imidazoles and boron-containing lithium salts. The additive phenylsulfonyl imidazole contains S elements and N elements, and can preferentially undergo a reduction reaction on the surface of the negative electrode plate 130. The SC bonds are preferentially broken to generate phenyl radicals and sulfonyl imidazoles. The phenyl radicals can promote the ring opening of ethylene carbonate (EC) in the cyclic carbonate in the electrolyte, which is beneficial to the formation of lithium carbonate inorganic salts from ethylene carbonate on the surface of the negative electrode plate 130. The lithium carbonate inorganic salt can improve the stability of the SEI film, thereby improving the high-temperature cycle performance of the SEI film. In addition, when phenylsulfonyl imidazoles participate in the formation of SEI film, there are multi-step reactions, which are not conducive to the construction of SEI film of negative electrode plate 130; the lone pair of electrons on the N atom of the imidazole ring in phenylsulfonyl imidazoles does not participate in conjugation, has nucleophilicity, and interacts with the electron-deficient B atom in the boron-containing lithium salt, so as to achieve the regulation of the reaction decomposition path of phenylsulfonyl imidazoles. Therefore, after adding boron-containing lithium salt, the reaction of phenylsulfonyl imidazole can be made more single, and the thickness uniformity of the generated SEI film will be better, so that the impedance distribution of SEI film is more uniform, and it is less likely to have partial analysis of lithium (because lithium is easily generated in places where the barrier is too large), thereby improving the stability of SEI film. Furthermore, boron-containing lithium salt is conducive to the formation of SEI film rich in nitrogen and sulfur elements on the surface of negative electrode plate 130. SEI film rich in nitrogen and sulfur elements has higher high temperature tolerance, so that the cycle performance of battery 100 can be better improved. Furthermore, by using phenylsulfonyl imidazole and boron-containing lithium salt additives together, the SEI film generated on the surface of the negative electrode plate 130 can contain imidazole organic polymers, phenyl organic polymers, Li3N and lithium sulfate. Imidazole organic polymers and phenyl organic polymers are beneficial to improving the flexibility of the SEI film and reducing the possibility of rupture of the SEI film during repeated lithium insertion and removal, thereby improving the high-temperature cycle performance of the battery 100. Inorganic salts such as Li3N and lithium sulfate can improve the heat resistance of the SEI film and reduce the solubility of the SEI film, thereby further improving the high-temperature cycle performance of the battery 100.
[0085] In some embodiments, the phenylsulfonyl imidazole has the following structural formula:
[0086]
[0087] Wherein, R1 is at least one of hydrogen, fluorine, methyl, trifluoromethyl, phenyl, isocyanate group, and vinyl group;
[0088] R2 is at least one of hydrogen, fluorine, methyl, trifluoromethyl, phenyl, isocyanate, and vinyl;
[0089] R3 is at least one of hydrogen, fluorine, methyl, trifluoromethyl, phenyl, isocyanate, and vinyl;
[0090] R4 is at least one of hydrogen, fluorine, methyl, trifluoromethyl, phenyl, isocyanate, and vinyl;
[0091] R5 is at least one of hydrogen, fluorine, methyl, trifluoromethyl, phenyl, isocyanate, and vinyl.
[0092] It should be noted that R1, R2, R3, R4, and R5 may be the same, or different, or partly the same and partly different. For example, R1, R2, R3, R4, and R5 are all hydrogen. For another example, R1, R2, R4, and R5 are all hydrogen, and R3 is at least one of methyl, fluorine, and trifluoromethyl.
[0093] The phenylsulfonyl imidazole additive of the structural formula of this embodiment can form more stable phenyl radicals when participating in the formation of SEI film, which can better promote the ring opening of ethylene carbonate (EC) in the cyclic carbonate in the electrolyte, which is conducive to the formation of lithium carbonate inorganic salt on the surface of the negative electrode plate 130 by ethylene carbonate. The lithium carbonate inorganic salt can improve the stability of the SEI film, thereby improving the high-temperature cycle performance of the SEI film. When the phenylsulfonyl imidazole of the structural formula is compounded with the boron-containing lithium salt, the reaction of the phenylsulfonyl imidazole can be made more single, and the thickness uniformity of the generated SEI film will be better, so that the impedance distribution of the SEI film is more uniform, and it is less likely to have partial analysis of lithium (because lithium precipitation is prone to occur in places where the barrier is too large), thereby improving the stability of the SEI film. Furthermore, the combined use of the two additives of phenylsulfonyl imidazole and boron-containing lithium salt in the present embodiment can make the SEI film generated on the surface of the negative electrode plate 130 contain components such as imidazole organic polymers, phenyl organic polymers, Li3N and lithium sulfate. The imidazole organic polymers and phenyl organic polymers are beneficial to improving the flexibility of the SEI film and reducing the possibility of rupture of the SEI film during repeated lithium insertion and de-lithiation, thereby improving the high-temperature cycle performance of the battery 100. Inorganic salts such as Li3N and lithium sulfate can improve the heat resistance of the SEI film and reduce the solubility of the SEI film, thereby further improving the high-temperature cycle performance of the battery 100.
[0094] In some embodiments, the phenylsulfonyl imidazole is a p-substituted phenylsulfonyl imidazole, and the substituent is one of an electron withdrawing group, a conjugated group, and a reactive group.
[0095] Optionally, the electron withdrawing group may be, but is not limited to, one of fluorine (-F), trifluoromethyl (-CF3), etc. The electron withdrawing group is arranged at the para position of the phenyl group, so that the lowest unoccupied molecular orbital (LUMO energy level) of the phenylsulfonyl imidazoles can be reduced, thereby increasing the reduction potential of the phenylsulfonyl imidazoles, so that the phenylsulfonyl imidazoles can better participate in the formation of the SEI film, and the fluorinated phenylsulfonyl imidazoles can increase the LiF component in the SEI film, thereby improving the thermal stability of the SEI film and improving the high temperature cycle performance of the battery 100.
[0096] Optionally, the conjugated group may be, but is not limited to, a benzene ring (or phenyl group). Compared with boron-containing lithium salts, phenylsulfonyl imidazoles may preferentially undergo a reduction reaction on the surface of the negative electrode plate 130, and the SC bond preferentially breaks to generate phenyl radicals and sulfonyl imidazoles. Phenyl radicals may promote the ring opening of ethylene carbonate (EC) in the cyclic carbonate in the electrolyte, which is beneficial for ethylene carbonate to generate lithium carbonate inorganic salts on the surface of the negative electrode plate 130, thereby improving the stability of the SEI film and thus improving the high-temperature cycle performance of the SEI film. The conjugated group may enhance the stability of the benzene radical, which is beneficial for promoting the ring opening of ethylene carbonate and improving the stability of the SEI film; in addition, the steric hindrance effect of the benzene ring may reduce the damage of the acid to the SEI film, thereby improving the acid resistance of the SEI film, and the acid production of the battery 100 at high temperatures may increase, thereby improving the high-temperature cycle performance of the battery 100.
[0097] Optionally, the reactive group may be, but is not limited to, a carbon-carbon double bond, which may participate in the reaction of the SEI film, thereby increasing the degree of polymerization of organic components in the SEI film, thereby increasing the thermal stability of the SEI film, reducing the solubility of the SEI film, and improving the cycle performance of the battery 100.
[0098] In some embodiments, the phenylsulfonyl imidazoles include at least one of the following structural formulas:
[0099] (phenylsulfonylimidazole), (p-methylphenylsulfonyl imidazole), (p-Fluorophenylsulfonyl imidazole), (p-Trifluoromethylphenylsulfonyl imidazole), (biphenylsulfonyl imidazole), (p-vinylphenylsulfonyl imidazole).
[0100] The phenylsulfonyl imidazole additive of this embodiment can form more stable phenyl radicals when participating in the formation of SEI film, which can better promote the ring opening of ethylene carbonate (EC) in the cyclic carbonate in the electrolyte, which is conducive to the formation of lithium carbonate inorganic salt on the surface of the negative electrode plate 130 by ethylene carbonate. The lithium carbonate inorganic salt can improve the stability of the SEI film, thereby improving the high-temperature cycle performance of the SEI film. When the phenylsulfonyl imidazole of this embodiment is compounded with the boron-containing lithium salt, the reaction of phenylsulfonyl imidazole can be made more single, and the thickness uniformity of the generated SEI film will be better, so that the impedance distribution of the SEI film is more uniform, and it is less likely to have partial analysis of lithium (because lithium precipitation is prone to occur in places where the barrier is too large), thereby improving the stability of the SEI film. Furthermore, the combined use of the two additives of phenylsulfonyl imidazole and boron-containing lithium salt in the present embodiment can make the SEI film generated on the surface of the negative electrode plate 130 contain components such as imidazole organic polymers, phenyl organic polymers, Li3N and lithium sulfate. The imidazole organic polymers and phenyl organic polymers are beneficial to improving the flexibility of the SEI film and reducing the possibility of rupture of the SEI film during repeated lithium insertion and de-lithiation, thereby improving the high-temperature cycle performance of the battery 100. Inorganic salts such as Li3N and lithium sulfate can improve the heat resistance of the SEI film and reduce the solubility of the SEI film, thereby further improving the high-temperature cycle performance of the battery 100.
[0101] In some embodiments, the boron-containing lithium salt includes at least one of lithium tetrafluoroborate, lithium bis(oxalatoborate), and lithium difluorooxalatoborate.
[0102] The boron-containing lithium salt of this embodiment can better regulate the multi-step reaction of phenylsulfonyl imidazoles, making the reaction of phenylsulfonyl imidazoles more simple, and the thickness uniformity of the generated SEI film will be better, so that the impedance distribution of the SEI film is relatively uniform, and it is less likely to have partial lithium analysis (because lithium precipitation is prone to occur in places where the obstruction is too large), thereby improving the stability of the SEI film. Furthermore, the boron-containing lithium salt of this embodiment is compounded with phenylsulfonyl imidazoles, so that the SEI film generated on the surface of the negative electrode plate 130 contains imidazole organic polymers, phenyl organic polymers, Li3N and lithium sulfate and other components. Imidazole organic polymers and phenyl organic polymers are beneficial to improving the flexibility of the SEI film and reducing the possibility of rupture of the SEI film during repeated lithium insertion and de-lithiation, thereby improving the high-temperature cycle performance of the battery 100. Inorganic salts such as Li3N and lithium sulfate can improve the heat resistance of the SEI film and reduce the solubility of the SEI film, thereby further improving the high-temperature cycle performance of the battery 100.
[0103] In some embodiments, in the electrolyte, the mass ratio A of the phenylsulfonyl imidazole to the boron-containing lithium salt is in the range of 0.05≤A≤4.0.
[0104] Specifically, the mass ratio A of the phenylsulfonyl imidazole to the boron-containing lithium salt in the electrolyte can be, but is not limited to, 0.05, 0.1, 0.2, 0.3, 0.4, 0.5, 0.6, 0.7, 0.8, 0.9, 1.0, 1.1, 1.2, 1.3, 1.4, 1.5, 1.6, 1.7, 1.8, 1.9, 2.0, 2.2, 2.4, 2.6, 2.8, 3.0, 3.2, 3.4, 3.6, 3.8, 4.0, etc.
[0105] In the present embodiment, if the mass ratio A of the phenylsulfonyl imidazole to the boron-containing lithium salt in the electrolyte is too small, the contents of Li2SO4 and lithium sulfonate in the SEI film formed by the negative electrode plate 130 of the battery 100 are low, which reduces the stability of the SEI film at high temperature, makes the SEI film easily dissolve, and reduces the acid resistance of the SEI film, thereby reducing the high temperature cycle performance of the battery 100; in addition, if the mass ratio A of the phenylsulfonyl imidazole to the boron-containing lithium salt in the electrolyte is too small, due to the electrostatic field interaction between the phenylsulfonyl imidazole and the boron-containing lithium salt, the boron-containing lithium salt cannot be quickly transferred to the interface of the negative electrode plate 130 with the phenylsulfonyl imidazole, and the boron-containing lithium salt cannot be replenished in time, resulting in a reduction in the reaction of the boron-containing lithium salt at the interface of the negative electrode plate 130, and more solvents participate in the formation of the SEI film, and the stability of the SEI film formed by the solvent is not as good as the stability of the SEI film formed by the boron-containing lithium salt, thereby reducing the high temperature cycle performance of the battery 100. If the mass ratio A of the phenylsulfonyl imidazole to the boron-containing lithium salt in the electrolyte is too large, the loose inorganic layer content in the SEI film is high, and the direct contact reaction between the electrolyte and the negative electrode active material in the negative electrode plate 130 cannot be effectively suppressed.
[0106] Furthermore, in the electrolyte, the mass ratio A of the phenylsulfonyl imidazole to the boron-containing lithium salt is in the range of 0.2≤A≤3. In this way, the phenylsulfonyl imidazole and the boron-containing lithium salt can better play a compounding role, and the formed SEI film has better heat resistance and acid resistance, so that the battery 100 has higher high-temperature cycle performance.
[0107] Furthermore, in the electrolyte, the mass ratio A of the phenylsulfonyl imidazole to the boron-containing lithium salt is in the range of 0.6≤A≤2. In this way, the phenylsulfonyl imidazole and the boron-containing lithium salt can better play a compounding role, and the formed SEI film has better heat resistance and acid resistance, so that the battery 100 has higher high-temperature cycle performance.
[0108] In some embodiments, in the electrolyte, the mass fraction a of the phenylsulfonyl imidazole is in the range of 0.05%≤a≤2.0%.
[0109] Specifically, in the electrolyte, the mass fraction a of the phenylsulfonyl imidazole can be but is not limited to 0.05%, 0.1%, 0.2%, 0.3%, 0.5%, 0.8%, 1%, 1.2%, 1.4%, 1.6%, 1.8%, 2%, etc.
[0110] In this embodiment, if the mass fraction a of the phenylsulfonyl imidazoles in the electrolyte is too low, the improvement of the heat resistance and acid resistance of the SEI film formed on the negative electrode plate 130 is limited, and the formed SEI film cannot effectively protect the negative electrode plate 130, which is not conducive to improving the high temperature cycle performance of the battery 100; if the mass fraction a of the phenylsulfonyl imidazoles in the electrolyte is too high, the thickness of the SEI film formed on the surface of the negative electrode plate 130 is too thick, which reduces the kinetic performance of the battery 100, makes the battery 100 prone to lithium precipitation and consumption of active lithium during the charge and discharge cycle, and in addition, it will increase the polarization of the battery 100, resulting in the loss of reversible lithium, thereby reducing the cycle performance of the battery 100.
[0111] In some embodiments, in the electrolyte, the mass fraction b of the boron-containing lithium salt is in the range of 0.05%≤b≤2.0%.
[0112] Specifically, in the electrolyte, the mass fraction b of the boron-containing lithium salt can be but is not limited to 0.05%, 0.1%, 0.2%, 0.3%, 0.5%, 0.8%, 1%, 1.2%, 1.4%, 1.6%, 1.8%, 2%, etc.
[0113] In this embodiment, if the mass fraction b of the boron-containing lithium salt in the electrolyte is too low, the component of inorganic matter in the SEI film on the surface of the negative electrode plate 130 is reduced, and the inorganic layer is prone to form a loose inorganic layer. If the content of the inorganic layer is too high, the formed SEI film cannot effectively protect the negative electrode plate 130, and the improvement of the high-temperature cycle performance of the battery 100 is limited; if the mass fraction b of the boron-containing lithium salt in the electrolyte is too high, the thickness of the SEI film formed on the surface of the negative electrode plate 130 is too thick, which reduces the kinetic performance of the battery 100, makes the battery 100 prone to lithium precipitation and consumption of active lithium during the charge and discharge cycle. In addition, it will increase the polarization of the battery 100 and cause the loss of reversible lithium, thereby reducing the cycle performance of the battery 100.
[0114] Optionally, the electrolyte salt is a lithium salt. The lithium salt includes at least one of lithium hexafluorophosphate (LiPF6), lithium tetrafluoroborate (LiBF4), lithium bis(fluorosulfonyl)imide (LiFSI), lithium bis(trifluoromethanesulfonyl)imide (LiTFSI), lithium bis(oxalatoborate) (LiBOB), lithium difluorobis(oxalatophosphate) (LiODFP), lithium difluorooxalatoborate (LiODFB), lithium difluorophosphate (LiPO2F2), lithium trifluoromethanesulfonate (CF3SO3Li), etc.
[0115] Optionally, in the electrolyte, the total molar concentration M of the lithium salt is in the range of 0.7mol / L≤M≤1.4mol / L. In the electrolyte, the total molar concentration M of the lithium salt may be, but is not limited to, 0.7mol / L, 0.8mol / L, 0.9mol / L, 1.0mol / L, 1.1mol / L, 1.2mol / L, 1.3mol / L, 1.4mol / L, etc. If the total molar concentration M of the lithium salt is too small, the concentration of free ions in the electrolyte is too small, which reduces the conductivity of the electrolyte and thus reduces the kinetic performance of the battery 100; if the total molar concentration M of the lithium salt is too large, it is easy for a part of the electrolyte salt to be undissociated, and the viscosity of the electrolyte will increase, which in turn reduces the conductivity of the electrolyte and also reduces the kinetic performance of the battery 100. When the total molar concentration M of the lithium salt in the electrolyte is in the range of 0.7 mol / L≤M≤1.4 mol / L, the electrolyte can have a higher conductivity, so that the battery 100 has better kinetic performance.
[0116] In some embodiments, the electrolyte further includes a sulfur-containing additive. Optionally, the sulfur-containing additive includes at least one of methylene disulfonate, ethylene sulfate, tris(trimethylsilyl)phosphite, propylene sultone, butyl sultone, and propylene sulfite. The sulfur-containing additive can form lithium sulfate or alkyl lithium sulfate on the positive electrode plate, which can further stabilize the cathode electrolyte interface film (Cathode Electrolyte Interphase, referred to as CEI film), and can make the solid electrolyte interface film of the positive electrode plate thinner, better reduce the impedance of the positive electrode plate, thereby reducing the high-temperature heat generation of the positive electrode plate and improving the safety performance of the battery 100. In addition, these sulfur-containing additives in this embodiment are less likely to decompose and produce acid when the battery 100 is at high temperature, which can better reduce the consumption of electrolyte at high temperature, so that the battery 100 maintains a high cycle capacity retention rate.
[0117] Optionally, in the electrolyte, the mass fraction w1 of the sulfur-containing additive is in the range of 0.1wt%≤w1≤1wt%. Specifically, in the electrolyte, the mass fraction w1 of the sulfur-containing additive may be, but is not limited to, 0.1wt%, 0.2wt%, 0.3wt%, 0.4wt%, 0.5wt%, 0.6wt%, 0.7wt%, 0.8wt%, 0.9wt%, 1wt%, etc. In the electrolyte, if the mass fraction w1 of the sulfur-containing additive is too low, the stability of the interface film of the positive electrode sheet is limited, and the safety performance of the battery 100 cannot be well improved; in the electrolyte, if the mass fraction w1 of the sulfur-containing additive is too high, the sulfur-containing additive is easily decomposed to produce acid under high temperature, destroying the interface film of the positive electrode sheet, so that the positive active layer of the positive electrode sheet is directly in contact with the electrolyte, increasing the side reaction between the positive active layer and the electrolyte, thereby increasing the consumption of the electrolyte and reducing the cycle capacity retention rate of the battery 100. When the mass fraction of the sulfur-containing additive in the electrolyte is 0.1wt%≤w1≤1wt%, the safety performance of the battery 100 can be better improved while maintaining a high cycle capacity retention rate of the battery 100.
[0118] Optionally, the electrolyte further includes a film-forming additive. When the electrolyte is applied to the lithium-ion battery 100, the film-forming additive can be used to promote the formation of an interface film of at least one of the positive electrode sheet and the negative electrode sheet 130 and maintain the stability of the interface film.
[0119] Optionally, the film-forming additive includes at least one of vinyl sulfate (DTD), vinylene carbonate (VC), vinyl carbonate (VEC), fluoroethylene carbonate (FEC), tris(trimethylsilyl) phosphate, tris(trimethylsilyl) borate, adiponitrile, succinonitrile, and 1,3,6-hexanetrinitrile.
[0120] Optionally, the mass fraction of the film-forming additive ranges from 1.5% to 3%. Specifically, the mass fraction of the film-forming additive may be, but is not limited to, 1.5%, 1.6%, 1.7%, 1.8%, 1.9%, 2%, 2.1%, 2.2%, 2.3%, 2.4%, 2.5%, 2.6%, 2.7%, 2.8%, 2.9%, 3%, etc.
[0121] Optionally, the electrolyte also includes an organic solvent. The organic solvent includes at least one of a cyclic carbonate and a chain carbonate. Cyclic carbonates have a high dielectric constant and high ionic conductivity, and can form a stable SEI film on the surface of the negative electrode plate 130, but their viscosity is relatively large. Chain carbonates have lower viscosity than cyclic carbonates, better electrochemical stability, and can improve the low-temperature performance of the electrolyte. Therefore, when a mixed solvent of cyclic carbonate and chain carbonate is used, the electrolyte can have a more suitable viscosity and low-temperature stability, and the battery 100 using the electrolyte can be better film-formed.
[0122] Optionally, the cyclic carbonate may include but is not limited to at least one of ethylene carbonate (EC for short), propylene carbonate (PC for short), etc. The dielectric constant of ethylene carbonate is much greater than that of propylene carbonate, and ethylene carbonate can better promote the formation of SEI film.
[0123] Optionally, the linear carbonate may include but is not limited to at least one of dimethyl carbonate (DMC for short), diethyl carbonate (DEC for short), ethyl methyl carbonate (EMC for short), and the like.
[0124] Optionally, in the electrolyte, the mass fraction of the organic solvent is 60wt% to 85wt%, specifically, but not limited to, 60wt%, 65wt%, 70wt%, 75wt%, 80wt%, 85wt%, etc.
[0125] Optionally, the organic solvent further comprises at least one of ethyl acetate, propyl acetate, ethyl propionate, propyl propionate, γ-butyrolactone, and 2,2-difluoroethyl acetate.
[0126] The electrolyte and the battery 100 of the present application are further described below through specific embodiments.
[0127] Examples 1 to 34, Comparative Examples 1 to 5
[0128] The preparation method of the battery 100 of each embodiment and comparative example includes:
[0129] (1) Preparation of positive electrode sheet 110: The positive electrode active material lithium iron phosphate (LiFePO4), conductive carbon black (positive electrode conductive agent, Super-P), and adhesive (positive electrode binder, PVDF) are dispersed in N-methylpyrrolidone (NMP) solvent according to a preset mass ratio, mixed evenly and prepared into a positive electrode slurry with a solid content of 60%; the positive electrode slurry is evenly coated on the surface of the positive electrode current collector 111 aluminum foil with a thickness of 10 μm, and the coating weight of the positive electrode slurry is 300 mg / 1540.25 mm 2After drying, cold pressing, slitting and cutting, the positive electrode slurry is solidified to form a positive electrode active layer 112, and a positive electrode sheet 110 is obtained, wherein the thickness of a single side of the positive electrode active layer 112 is 100 μm;
[0130] (2) Preparation of negative electrode sheet 130: Graphite (negative electrode active material), sodium carboxymethyl cellulose (negative electrode thickener, referred to as CMC), styrene butadiene rubber latex (negative electrode binder SBR), and asphalt are dispersed in deionized water according to a preset mass ratio and prepared into a negative electrode slurry with a solid content of 50%. The negative electrode slurry is evenly coated on a copper foil of the negative electrode current collector 131 with a thickness of 6 μm. The coating weight of the negative electrode slurry is 144 mg / 1540.25 mm 2 After drying, cold pressing, slitting and cutting, the negative electrode slurry is solidified to form a negative electrode active layer 132, and a negative electrode sheet 130 is obtained, wherein the thickness of a single side of the negative electrode active layer 132 is 70 μm;
[0131] (3) Preparation of electrolyte: In an argon atmosphere glove box with a moisture content of ≤1ppm, ethylene carbonate (EC), dimethyl carbonate (DMC), and ethyl methyl carbonate (EMC) are mixed in a mass ratio of 1:1:1 to obtain a mixed solvent, and then dry electrolyte salt lithium hexafluorophosphate is dissolved in the mixed solvent and stirred until completely dissolved and uniformly dissolved, and additives such as vinylene carbonate (VC), fluoroethylene carbonate (FEC), and vinyl sulfate (DTD) are added and stirred uniformly, and phenylsulfonyl imidazoles and boron-containing lithium salts are added and stirred uniformly to obtain an electrolyte, wherein the molar concentration of lithium hexafluorophosphate in the electrolyte is 1 mol / L, and the types and addition amounts of phenylsulfonyl imidazoles and boron-containing lithium salts in each embodiment and comparative example are shown in Table 1 below;
[0132] (4) Preparation of the separator 120 : A 16 μm polyethylene film was used as the separator 120 .
[0133] (5) Assembly of battery 100: The positive electrode sheet 110, the separator 120, and the negative electrode sheet 130 are stacked in sequence to form an electrode assembly, and the electrode assembly is wound to obtain a bare cell. After welding the tabs, the cell is assembled into an outer package, and after injecting the above-mentioned electrolyte, vacuum packaging, standing, forming, shaping, capacity testing, etc. are performed to finally prepare battery 100.
[0134] The performance test was performed on the battery 100 of each embodiment and comparative example:
[0135] (1) 45℃ cycle performance test: Under 45℃ environment, let the initialized battery 100 stand for 5h; charge to 3.65V at 1P constant power, let stand for 10 minutes; discharge to 2.5V at 1P constant power, let stand for 10 minutes; such a charge-discharge process is called a cycle process or a cycle. 1P constant power charging / 1P constant power discharge is used to perform a small cycle performance test on the battery 100, record the discharge capacity of the battery 100 after 1000 cycles, and calculate the cycle capacity retention rate of the battery 100 after 1000 cycles. Cycle capacity retention rate = (discharge capacity of the 1000th cycle / initial discharge capacity C0) × 100%.
[0136] The initial discharge capacity percentage of the battery 100 of each embodiment and comparative example and the cycle capacity retention rate after 1000 cycles at 45° C. and a charge and discharge rate of 1P are shown in Table 1 below.
[0137] Table 1 Performance parameters of the battery 100 of each embodiment and comparative example
[0138]
[0139]
[0140] It can be seen from the test results of Comparative Example 1 that the electrolyte in Comparative Example 1 does not add phenylsulfonyl imidazole additives and does not add boron-containing lithium salt additives, and the capacity retention rate of the battery 100 after 1000 cycles at 45°C is low. This may be because during the cycle of the battery 100, as the battery 100 is charged and discharged, the electrochemical process is accompanied by the expansion and contraction process of the SEI film of the negative electrode plate 130. At this time, the SEI film has poor cycle stability at high temperature. Therefore, the SEI film is constantly destroyed and repaired. The process of generating the SEI film is the process of the electrolyte components gaining and losing electrons on the surface of the negative electrode active layer 132. This process is accompanied by the loss of active lithium, and it is an irreversible loss. The reduction in the active lithium content leads to a reduction in the charge and discharge cycle capacity of the battery 100.
[0141] It can be seen from the test results of Comparative Examples 2 and 3 that the addition of phenylsulfonyl imidazole additives (such as Comparative Example 2) or the addition of boron-containing lithium salt additives (such as Comparative Example 3) can improve the high-temperature cycle capacity retention rate of battery 100. However, the improvement in the high-temperature cycle capacity retention rate of battery 100 is relatively limited.
[0142] The electrolytes in Example 1 and Example 21 were added with phenylsulfonyl imidazole additives and boron-containing lithium salt additives at the same time, and the capacity retention rate of the battery 100 after 1000 cycles at 45°C was greatly improved. This shows that compared with the use of phenylsulfonyl imidazole additives alone or the use of boron-containing lithium salt additives alone, the addition of phenylsulfonyl imidazole additives and boron-containing lithium salt additives can better improve the high-temperature cycle capacity retention rate of the battery 100.
[0143] From the test results of Examples 1 to 20 and Comparative Example 4, it can be seen that when the amount of boron-containing lithium salt added remains unchanged, as the content of phenylsulfonyl imidazole additives increases, the cycle capacity retention of battery 100 at high temperature first gradually increases and then gradually decreases. When the mass fraction of phenylsulfonyl imidazoles is 0.05% to 2%, battery 100 has a higher high-temperature cycle capacity retention rate. When the mass fraction of phenylsulfonyl imidazoles is 0.5% to 2%, the high-temperature cycle capacity retention rate of battery 100 is further improved.
[0144] From the test results of Examples 21 to 24 and Comparative Example 5, it can be seen that when the amount of phenylsulfonyl imidazole additives added remains unchanged, as the content of boron-containing lithium salt increases, the cycle capacity retention of battery 100 at high temperature first gradually increases and then gradually decreases. When the mass fraction of boron-containing lithium salt is 0.05% to 2%, battery 100 has a higher high-temperature cycle capacity retention rate. When the mass fraction of boron-containing lithium salt is 0.5% to 2%, the high-temperature cycle capacity retention rate of battery 100 is further improved.
[0145] From the test results of Example 3, Example 7, Example 10, Example 13, Example 16 and Example 19, it can be seen that when the phenylsulfonyl imidazole contains a F substituent, a trifluoromethyl group, a benzene ring or a vinyl group, the cycle capacity retention rate of the battery 100 can be better improved. Fluorine-containing and trifluoromethyl groups are electron-withdrawing groups, and electron-withdrawing groups are arranged at the para position of the phenyl group, which can reduce the LUMO energy level of the phenylsulfonyl imidazoles, thereby increasing the reduction potential of the phenylsulfonyl imidazoles, so that the phenylsulfonyl imidazoles can better participate in the formation of the SEI film, and the fluorine-containing phenylsulfonyl imidazoles can increase the LiF component in the SEI film, thereby improving the thermal stability of the SEI film and improving the high temperature cycle performance of the battery 100. The benzene ring can be used as a conjugated group, which can improve the stability of the benzene free radical, promote the ring opening of ethylene carbonate, and improve the stability of the SEI film; in addition, the steric hindrance effect of the benzene ring can reduce the damage of the acid to the SEI film, thereby improving the acid resistance of the SEI film, and the acid production of the battery 100 at high temperature will increase, thereby improving the high temperature cycle performance of the battery 100. The vinyl group can participate in the reaction of the SEI film and increase the degree of polymerization of the organic components in the SEI film, thereby improving the thermal stability of the SEI film, reducing the solubility of the SEI film, and improving the cycle performance of the battery 100.
[0146] It can be seen from the test results of Example 3, Example 25 and Example 26 that when the type and content of phenylsulfonyl imidazoles are the same, the effect of using lithium difluorooxalatoborate is better than that of lithium bis(oxalatoborate) and lithium tetrafluoroborate. The main reason is that the SEI formed with the participation of lithium difluorooxalatoborate is rich in LiF and Li2CO3 components. Compared with a single component, the rich SEI component can improve the density and thermal stability of the SEI, thereby making the battery 100 have a higher high-temperature cycle capacity retention rate.
[0147] It can be seen from the test results of Example 27 to Example 34 that as the mass ratio A of the phenylsulfonyl imidazole to the boron-containing lithium salt increases, the high temperature cycle capacity of the battery 100 first gradually increases and then gradually decreases; when the mass ratio A of the phenylsulfonyl imidazole to the boron-containing lithium salt is 0.1 to 2.0, the combination of phenylsulfonyl imidazole and lithium bis(oxalate borate) has a better improvement effect. The main reason is that within the selected range, phenylsulfonyl imidazole and lithium bis(oxalate borate) can interact through the electrostatic field and migrate to the negative electrode surface to jointly participate in the construction of SEI, making the components of the SEI film richer and improving stability. When the A value is too small or too large, the electrolyte components involved in the construction of SEI are relatively single, and the generated SEI film components are single, which is not conducive to improving the stability of the SEI film.
[0148] Mentioning "embodiment" and "implementation method" in this application means that the specific features, structures or characteristics described in conjunction with the embodiment may be included in at least one embodiment of the present application. The appearance of the phrases in various places in the specification does not necessarily refer to the same embodiment, nor is it an independent or alternative embodiment that is mutually exclusive with other embodiments. It is explicitly and implicitly understood by those skilled in the art that the embodiments described in this application can be combined with other embodiments. In addition, it should also be understood that the features, structures or characteristics described in the various embodiments of the present application can be arbitrarily combined to form another embodiment that does not deviate from the spirit and scope of the technical solution of the present application, provided that there is no contradiction between them.
[0149] Finally, it should be noted that the above implementation modes are only used to illustrate the technical solution of the present application and are not intended to limit it. Although the present application has been described in detail with reference to the above preferred implementation modes, a person of ordinary skill in the art should understand that the technical solution of the present application may be modified or replaced by equivalents without departing from the spirit and scope of the technical solution of the present application.
Claims
1. An electrolyte, characterized in that: The electrolyte includes electrolyte salt, phenylsulfonyl imidazoles and boron-containing lithium salt.
2. The electrolyte according to claim 1, characterized in that The structural formula of the phenylsulfonyl imidazoles is as follows: Wherein, R1 is at least one of hydrogen, fluorine, methyl, trifluoromethyl, phenyl, isocyanate group, and vinyl group; R2 is at least one of hydrogen, fluorine, methyl, trifluoromethyl, phenyl, isocyanate, and vinyl; R3 is at least one of hydrogen, fluorine, methyl, trifluoromethyl, phenyl, isocyanate, and vinyl; R4 is at least one of hydrogen, fluorine, methyl, trifluoromethyl, phenyl, isocyanate, and vinyl; R5 is at least one of hydrogen, fluorine, methyl, trifluoromethyl, phenyl, isocyanate, and vinyl.
3. The electrolyte according to claim 1, characterized in that The phenylsulfonyl imidazoles are p-substituted phenylsulfonyl imidazoles, and the substituent is one of an electron withdrawing group, a conjugated group, and a reactive group.
4. The electrolyte according to claim 1, characterized in that The phenylsulfonyl imidazoles include at least one of the following structural formulas:
5. The electrolyte according to claim 1, characterized in that The boron-containing lithium salt includes at least one of lithium tetrafluoroborate, lithium bis(oxalatoborate) and lithium difluorooxalatoborate.
6. The electrolyte according to claim 1, characterized in that In the electrolyte, the mass ratio A of the phenylsulfonyl imidazole to the boron-containing lithium salt is in the range of 0.05≤A≤4.
0.
7. The electrolyte according to claim 6, characterized in that In the electrolyte, the mass ratio A of the phenylsulfonyl imidazole to the boron-containing lithium salt is in the range of 0.6≤A≤2.
8. The electrolyte according to claim 6, characterized in that In the electrolyte, the mass fraction a of the phenylsulfonyl imidazoles is in the range of 0.05%≤a≤2.0%.
9. The electrolyte according to claim 6, characterized in that In the electrolyte, the mass fraction b of the boron-containing lithium salt is in the range of 0.05%≤b≤2.0%.
10. A battery, characterized in that: include: The electrolyte, positive electrode sheet, separator and negative electrode sheet as described in any one of claims 1 to 9.
11. An energy storage device, characterized in that: include: Box; as well as A plurality of batteries according to claim 10, wherein the plurality of batteries are housed in the casing.
12. An energy storage system, characterized in that: include: The energy storage device according to claim 11; as well as An electric energy conversion device, wherein the electric energy conversion device is electrically connected to the energy storage device, the electric energy conversion device is used to convert other forms of energy into electric energy, and the energy storage device is used to store the electric energy.
Citation Information
Patent Citations
Anti-overcharge electrolyte and lithium ion battery using same
CN111244545A
Electrolyte, battery and power utilization system
CN117712487A
Electrolyte, secondary battery containing electrolyte, battery pack and electric equipment
CN117878408A
Electrolyte, battery, energy storage device and energy storage system
CN118841628A
Online game-linked system for emotional classification data using brain waves
KR1020250084636A